Phytochrome controls achene germination in Bidens pilosa L. (Asteraceae) by very low fluence response - Amaral-Baroli, Adriana [UNESP]; Takaki, Massanori [UNESP] (Brazilian Archives of Biology and Technology, 2001)
Aquênios sem ornamento do tegumento são insensíveis à luz com ocorrência de germinação sob todas as condições de luz testadas. Aquênios com ornamento verrucoso do tegumento apresentou baixa germinação sob escuro e alta germinação sob luz. A pré-incubação a 36° C para a remoção de Fve pré-existente e pela comparação dos resultados de contagem no final do experimento de aquênios que germinam no escuro e diárias sob luz verde de segurança (0.001mimol m-2s-1nm-1) concluimos que a germinação de Bidens pilosa é controlada pelo fitocromo através da resposta de fluência baixa.

Achene without ornament of the tegument were light insensitive with germination under all tested light conditions. Achene with verrucose ornament of the tegument presented low germination under darkness and high germination under light conditions. By pre-incubation at 36° C for remotion of pre-existing Pfr and by comparison of results of counting of dark germinating achenes at the end of experiment and daily under dim green safe light (0.001mumol m-2 s-1 nm-1) we concluded that germination was controlled by phytochrome through very low fluence response.
Keywords: Bidens pilosa; phytochrome; VLFR; achene germination